Occupational stress and work engagement among primary healthcare physicians: a cross-sectional study - Lourenção, Luciano Garcia; Sodré, Paula Canova; Gazetta, Cláudia Eli; Silva, Albertina Gomes da; Castro, Jussara Rossi; Maniglia, José Victor (São Paulo Medical Journal, 2022)
BACKGROUND: Brazil’s Family Health Strategy is based on a primary healthcare model, which is considered to have case resolution capacity, with physicians at its center. OBJECTIVES: To evaluate the levels of occupational stress and work engagement among primary health- care physicians. DESIGN AND SETTING: Cross-sectional study conducted in 2017, in São José do Rio Preto, São Paulo, Brazil. METHODS: A non-probability sample including 32 physicians from family health teams was used. Three self-applied instruments were used: a scale developed by the researchers seeking sociodemographic and professional variables, the Work Stress Scale and the Utrecht Work Engagement Scale. RESULTS: Female professionals (59.4%), permanent employees (56.3%), workload of 40 hours per week (59.4%) and 3-10 years of acting in primary care (68.8%) were more prevalent. Six professionals (19.4%) exhibited significant stress (score ≥ 2.5). The main stressors were lack of prospects for career growth (2.9 ± 1.3), form of task distribution (2.7 ± 1.0), poor training (2.7 ± 1.2) and insufficient time to perform the job (2.6 ± 1.2). Levels of work engagement ranged from 4.3 to 4.6 and were rated as high in all dimensions. Physicians with occupational stress had average levels of work engagement, whereas those without occupational stress had high levels of work commitment. CONCLUSIONS: A notable percentage of the physicians were experiencing occupational stress. The physicians had high levels of work engagement. Occupational stress was negatively correlated with work engagement, and it significantly compromised physicians’ levels of work engagement and interfered with their positive relationship with the work environment.